Developing supply chain resilience through integration: An empirical study on an e‐commerce platform. Issue 3 (27th November 2022) - Qi, Yinan; Wang, Xiaorui; Zhang, Min; Wang, Qiang
Abstract: The outbreak of the COVID‐19 pandemic has disrupted supply chains and increased the uncertainties faced by firms. While firms are struggling to survive and recover from the pandemic, Chinese e‐commerce platforms have demonstrated resilient supply chains. We develop a framework that investigates the impacts of integration between an e‐commerce platform and suppliers on supply chain resilience and the moderating effect of the suppliers' product flexibility. An analysis of data from a Chinese e‐commerce platform using operational indicators finds that integration between the e‐commerce platform and suppliers in terms of information sharing, joint planning and logistics cooperation has positive impacts on supply chain resilience, while procurement automation has the opposite effect. Furthermore, product flexibility positively moderates the impacts of information sharing, joint planning and logistics cooperation. The results enhance current understandings of the factors that contribute to the development of supply chain resilience and reveal that the relationship between integration and resilience should be examined within a contingency framework. The findings also provide guidelines for managers taking measures to mitigate the negative influences of supply chain disruptions.